EFFECTS OF MICROWAVE POWER AND SLICE THICKNESS ON FIBER AND ASH CONTENTS OF DRIED SWEET POTATO (IPOMOEA BATATA) (Nigerian Journal of Technology, 2020)
Investigation of microwave drying of sweet potato slices was conducted at microwave oven  power settings of 90, 100, 120 Watts and slice thicknesses of 3mm, 4mm and 6mm using Fourier models and response surface methods. The slice samples dried from initial moisture content of 70.71 to 12.7 final (equilibrium) moisture content in the microwave oven. Fourier models adequately fitted the drying data with the following values of the fit parameters: MBE= 0.00002943 to 0.000645, R² = 0.9987 to 1, RMSE = 0.00384 to 0.01692. Effective moisture diffusion coefficient ( of the samples ranged from m2/s to  m2/s. Analysis of Variance (ANOVA) was used to analyze the effect of drying conditions on the samples parameters at 95% ( p